1997
DOI: 10.1038/sj.sc.3100404
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic spinal cord injuries in Southeast Turkey: an epidemiological study

Abstract: In 1994, a retrospective study of new cases of traumatic Spinal Cord Injury (SCI) was conducted in all the hospitals in Southeast Turkey: 75 new traumatic SCI were identi®ed. The estimated annual incidence was 16.9 per million population. The male/female ratio was 5.8/1. The mean age was 31.3, being 31.25 for male patients and 31.36 for female patients. 70.7% of all patients were under the age of 40. The major causes of SCI were falls (37.3%) and gunshot wounds (29.3%), followed by car accidents (25.3%), and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
54
1
3

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(63 citation statements)
references
References 12 publications
5
54
1
3
Order By: Relevance
“…Our study showed a preponderance of males less than 40 years of age affected by SCI. This finding is buttressed by other studies 3,5,9 and further highlights the devastating effect of SCI on the economy due to the loss of productivity following invalidation, death or disability on this young vital productive sector of the economy. The adverse effects of SCI are not limited to the individual; it also affects the family, health facility, society and national economy.…”
Section: Discussionmentioning
confidence: 74%
“…Our study showed a preponderance of males less than 40 years of age affected by SCI. This finding is buttressed by other studies 3,5,9 and further highlights the devastating effect of SCI on the economy due to the loss of productivity following invalidation, death or disability on this young vital productive sector of the economy. The adverse effects of SCI are not limited to the individual; it also affects the family, health facility, society and national economy.…”
Section: Discussionmentioning
confidence: 74%
“…The high incidence of cervical injuries in Japan further supports this judgement. 16 There is no cervical injury before the age of 30 simply because they were well protected. In contrast to western people, Chinese are not keen to take physical risk at this stage when safe earning is the priority of their life.…”
Section: Discussionmentioning
confidence: 99%
“…Gunshot injury is a common cause in certain countries. 8,17,18 Accidental gunfire was the second largest reason for TSCI in Jordan, because firing random shots in the air was a common cultural habit during the celebrations of wedding parties in rural areas. 8 In China, firearms are strictly controlled, so such injury was scarce.…”
Section: Discussionmentioning
confidence: 99%